Implementation of Handover and Savings of Print and Record Works Policy at the Library of South Sumatra - Defa, Anprema; Alfatih, Andy; Ermanovida (HM Publisher, 2018)
It was known that there were lack of order mandatory submission in Local Library of South Sumatra. Implementation of handover and savings of print and record work policy was one of the steps of South Sumatera Provincial Government to preserve the work of the region. This implementation was very influential in determining the quality of local policies or regulations. The purpose of this study was to find out how many local works produced by South Sumatera Province. This research used qualitative research method with descriptive form. Data collected via interview to key informants, observation and literature study using Ripley and Franklin's theories of compliance, the smoothness of the function routines and the realization of the desired performance and its impact. The first dimension of compliance level had indicated the implementation of the handover and the saving of the work in the Library Board of South Sumatera Province, the second dimension of the smoothness of the function routine was the implementation of socialization and the data collection of published works, and the last dimension is the increasing of knowledge and the amount of work received at Delivery of Print Works and Record Works at the Library Board of South Sumatra Province. Indicators of this study can be concluded that the three dimensions used are quite ideal.